Preparation of polymeric micelles for use as carriers of tuberculostatic drugs - Silva, Marcia [UNESP]; Ferreira, Eiizabeth I.; Leite, Clarice Queico Fujimura [UNESP]; Sato, Daisy N. (Pharmacotherapy Group, 2007)
Purpose: This paper focuses on the characterization of polymeric micelle-forming tuberculostatic prodrugs and the antimycobacterial activity of these prodrugs.Method: By the condensation of hydroxymethylpyrazinamide, isoniazid and rifampin with free carboxyl groups on the copolymer poly(ethyleneglycol)-poly(aspartic acid), micelle-forming carrier-drug conjugates were obtained. These micelles were characterized by dynamic light scattering, to measure the micelle diameter; by acid-base titration, to determine the percentage of carboxylic groups occupied by the tuberculostatic; by Sudan III solubility tests, to estimate the critical micelle concentration (CMC); and visual control and spectrophotometric measurement, to determine the stability of micelles. These micelles were tested in vitro against several Mycobacterium strains.Results: As expected, the size and distribution of the micelle-forming tuberculostatic prodrugs found to be small (78.2nm, 84.2nm and 98.9 nm) while the level of the drug conjugated was high (65.02-85.7%). Furthermore, the micelles were stable in vitro, exhibiting a low level of CMC and stronger antimycobacterial activity than the original drugs.Conclusion: the results demonstrate that polymeric micelles can be used as efficient carriers for drugs, which alone, exhibit undesired pharmacokinetics, poor solubility, and low stability. The synthesized micelle-forming tuberculostatic prodrugs opens a perspective of alternative prodrugs that prolong action and decrease the toxicity of the tuberculostatic drugs of choice.
Keywords: pyrazinamide; isoniazid; rifampin; tuberculostatic prodrugs; polymer micelles